Quantifying Anionic Diffusion in 2D Halide Perovskite Lateral Heterostructures. Issue 51 (15th October 2021) - Akriti; Zhang, Shuchen; Lin, Zih‐Yu; Shi, Enzheng; Finkenauer, Blake P.; Gao, Yao; Pistone, Alan J.; Ma, Ke; Savoie, Brett M.; Dou, Letian
Abstract: Anionic diffusion strongly impacts the stability of halide perovskite materials, but it is still not well understood. Here, a quantitative investigation of in‐plane thermally driven anionic inter‐diffusion in a series of novel 2D and quasi‐2D halide perovskites lateral heterostructures is reported. The calculated diffusion coefficients ( D ) reveal the inhibition of Br–I inter‐diffusion with bulky π‐conjugated organic cations compared with short‐chain aliphatic organic cations. Furthermore, halide diffusion is found to be faster in quasi‐2D ( n  > 1) than 2D perovskites ( n  = 1). The increment becomes less apparent as the " n " number increases, akin to the quantum confinement effect observed for band gaps. These trends are rationalized by molecular dynamics simulations of free energy barriers for halide diffusion that reveal mechanisms for suppressing diffusion. This work provides important fundamental insights on the anionic migration and diffusion process in halide perovskite materials. Abstract : A library of 2D and quasi‐2D halide perovskite lateral heterostructures is synthesized, and the platform is utilized to analyze the impact of organic cation and inorganic layer thickness on bromide–iodide interdiffusion kinetics. This quantitative halide diffusion study on perovskites will aid in driving future innovations toward novel material design and optoelectronic device applications.